A Method to the Madness: The Revolutionary Marxist Method of Deleuze and Guattari - Culp, Andrew (Stasis, 2019)
In this article, Andrew Culp looks to how Gilles Deleuze and Félix Guattari flip Marxism on its head. He makes the case by drawing on Marx’s own distinction between the dialectical mode of presentation and research-based mode of inquiry that went into writing Capital, which leads him to consult the prefaces and afterwords to Capitalin addition to Marxist feminists who discuss the book’s sensational style. Culp then argues that Deleuze and Guattari’s most significant contribution to Marxism is a methodological one, as found in their critical and clinical anthropology, which outlines the universal history of capitalism (diagrammed by Culp in an included chart). The result, he maintains, frees images of radical change from dialectics, liberal democracy, markets, or production as engines of revolution. In their place, he locates a new critique of political economics based on the destruction of economics itself by way of a revolution of the outside.